The Safer Delivery of Surgical Services Program (S3): Explaining Its Differential Effectiveness and Exploring Implications for Improving Quality in Complex Systems. Issue 6 (December 2016) - Flynn, Lorna C.; McCulloch, Peter G.; Morgan, Lauren J.; Robertson, Eleanor R.; New, Steve J.; Stedman, Francesca E.; Martin, Graham P.
Abstract : Objective: To analyze the challenges encountered during surgical quality improvement interventions, and explain the relative success of different intervention strategies. Summary Background Data: Understanding why and how interventions work is vital for developing improvement science. The S3 Program of studies tested whether combining interventions addressing culture and system was more likely to result in improvement than either approach alone. Quantitative results supported this theory. This qualitative study investigates why this happened, what aspects of the interventions and their implementation most affected improvement, and the implications for similar programs. Methods: Semistructured interviews were conducted with hospital staff (23) and research team members (11) involved in S3 studies. Analysis was based on the constant comparative method, with coding conducted concurrently with data collection. Themes were identified and developed in relation to the program theory behind S3. Results: The superior performance of combined intervention over single intervention arms appeared related to greater awareness and ability to act, supporting the S3 hypothesis. However, we also noted unforeseen differences in implementation that seemed to amplify this difference. The greater ambition and more sophisticated approach in combined intervention arms resulted in requests for more intensive expert support, which seemed crucial in their success. The contextual challenges encountered have potential implications for the replicability and sustainability of the approach. Conclusions: Our findings support the S3 hypothesis, triangulating with quantitative results and providing an explanatory account of the causal relationship between interventions and outcomes. They also highlight the importance of implementation strategies, and of factors outside the control of program designers. Abstract : Supplemental Digital Content is available in the text